FAKE NEWS, SOCIAL MEDIA AND NATIONAL SECURITY: WORLD VIEW AND ISLAMIC PERSPECTIVE - Muhammad, Abdulqadir Sulaiman; Ismail, Bashir Abdullah; Muhammad, Diya’uddeen Balarabe (PT. Antis International Publisher, 2025)
Objective: This study aims to explore the critical relationship between the proliferation of fake news on social media and its implications for national security, while proposing an Islamic ethical framework as a comprehensive strategy to mitigate these challenges. Method: Using a qualitative approach, the research conducts textual analysis of primary Islamic sources—namely the Qur’an, Hadith, and classical scholarly interpretations—to identify ethical principles relevant to information integrity. Results: The findings reveal that Islamic values such as ṣidq (truthfulness), tabayyun (verification), and the prohibition of kadhib (falsehood) and namimah (slander) form a robust foundation for countering digital misinformation. These principles translate into practical frameworks encompassing policy-level interventions guided by maslaha (public interest) and hisbah (public accountability), as well as communal and individual measures emphasizing digital taqwa (God-consciousness). Novelty: This study uniquely integrates Islamic ethics with modern counter-disinformation strategies, offering a spiritually grounded, culturally relevant, and context-sensitive framework that strengthens social cohesion and national resilience against the spread of fake news in Muslim-majority societies and beyond.